The People versus Behavioral Science: Alignment between lay and scientific understanding of compliance - Christopher P. Reinders Folmer; Malouke E. Kuiper; Benjamin van Rooij (PLoS ONE, 2026)
Since the beginning of the 21 st century, behavioral insights have increasingly been used to inform policy. However, rather than land in a vacuum, such insights arrive in a setting where the citizens they target themselves have lay understanding of what shapes behavior—an understanding that may critically shape their endorsement of such policies. As such, to change behavior through behavioral science, people’s lay understanding is of pivotal importance. Yet so far, we know little about how laypersons think about changing behavior, or whether their lay understanding of this aligns with that of science. The present research examines this question by focusing on rule compliance, a frequent target of behavioral influence. In a large-scale survey (N = 3326), we assess participants’ lay perceptions of how compliance is shaped by different mechanisms identified in the academic literature, and compare this to empirically observed associations. For this purpose, we focused on behavioral measures against COVID-19—newly introduced rules that applied universally, where behavioral insights were widely utilized to promote compliance, and ample empirical data exists on relevant mechanisms. Our findings revealed that at the aggregate level, there was substantial concordance between participants’ lay understanding of how different mechanisms contributed to compliance and empirical evidence—although participants seem to overestimate their impact in absolute terms, and underestimate their variability. While this result need not imply that laypersons individually have an accurate understanding of what shapes compliance, it does suggest that collectively, people’s lay understanding of these processes was broadly aligned with a scientific understanding. Moreover, their lay understanding of these processes was associated with their preferences for policies to shape compliance by leveraging these mechanisms. In this way, people’s lay understanding may provide a stepping stone for scientifically informed policies—and an important reservoir of experiential knowledge that the science of behavior change can tap into.